American fanatics / Dorothy Barresi. - Barresi, Dorothy (Pitt poetry series., 2010)
"American Fanatics is driven by a diction that is electrifyingly alive with the idiosyncratic pulse of our strange particular historical moment that includes pet dogs slaughtered by coyotes, mystical Vietnamese nail salon workers, and ephebiphobiacs wandering our sunny streets; these poems enchant and inspire. Part hip metaphysician, part late corrupted dharma bum, Dorothy Barresi is also Simic- or Marquez-like in her regard for the world, which allows her to evoke a magically realistic panarama that comes to resemble, as we make our way through this wonderful book, our own entropic world. I haven't been this excited an optimistic about the state of American poetry in a long time, and I can't wait for you to read this book."--Bruce Weigl.